The Daiwa Bank Case (1999) - Yamada, Tsuyoshi (Columbia Journal of Asian Law, 2002)
The following is a summary translation of a representative action brought by Daiwa Bank’s stockholders against the Bank regarding the New York Daiwa Bank scandal. A Daiwa bond trader covered up $1.1 billion.in losses incurred through illegal trades over the course of eleven years. This case was decided by the Osaka district court, and it had a very strong impact not only among corporate directors, but also all over Japan, because directors of Daiwa Bank were ordered to pay approximately $775 million. This was first court decision that ordered directors to pay such a huge amount of money, and it fostered much debate about the derivative action system in Japan. Directors’ groups and some politicians insisted that compensation be limited to two years salary of the director. The case was divided into two parts, Case A and Case B. The Court found that the directors of Daiwa bank had a duty to establish a proper risk management system, but failed to do so. A proper risk management system would have included separation of front office from back office, and also of U.S. Treasury bill dealing business from custodian business. It also would have included the confirmation of a balance of U.S. Treasury bills in custody.